Pengembangan latihan imagery tahapan periodisasi kompetisi untuk atlet pencak silat tunggal mahasiswa - Okki Fitria Bella Alfareza; Kurniati Rahayuni (Physical Education Departement of University PGRI Jombang, 2025)
Imagery training is an effective training method for increasing athletes' peak performance by visualizing or mentally imagining movements. In imagery training, the training intensity during the competition period is around 80%. However, around 75-80% of an athlete's peak performance is still influenced by proper physical preparation, technique, tactics and strategy. Imagery training allows athletes to reconstruct movement experiences in their minds, so they can represent those movement patterns accurately. This process involves observation, attention and imagining certain movement patterns which are then stored in the brain's memory, in order to increase concentration and understanding of the technique. The process of this imagery development method includes 1) observation and interviews, 2) product design, 3) expert evaluation, 4) small group trials, 5) large group trials, 6) final product. The final result of the product is a 10 minute audio-visual spectrum which has a series of features from the moment the athlete prepares to enter the competition arena, until they get maximum results. This research involved 7 (seven) adult single category pencak silat athletes and 3 (three) pencak silat trainers at the State University of Malang. Small group trials obtained 100% results in aspects of suitability of rhythm and tone, 100% in aspects of attractiveness and suitability for use in the adult age category, and 100% in aspects material of continuity. Meanwhile, in the large group trial, results were 100% in the suitability aspect of self-reflection. Based on expert tests, small group tests and large group trials, this audio-visual spectrum product is suitable for use in training during competitions.